ANALISIS STRUKTUR DAN MAKNA FUKUSHI IYOIYO, TOUTOU DAN YATTO: TINJAUAN LINGUISTIK KOMPARATIF 副詞「いよいよ」,「とうとう」,「やっと」の構成と意味の分析:比較言語学的考察 - Lukman Alatas; Teguh Santoso2 (Universitas Ngudi Waluyo, 2025)
In Japanese fukushi iyoiyo, toutou and yatto when translated into Indonesian have the same meaning, namely